To rewrite the equation \( 52x - 8 - 1 = 9 \) as two equations joined by "and," we first simplify the original equation:
-
Combine like terms:
\( 52x - 9 = 9 \) -
Set the equation equal to the number on the right side:
\( 52x - 9 = 9 \)
Now add 9 to both sides:
\( 52x = 18 \)
Next, divide both sides by 52:
\( x = \frac{18}{52} \)
Simplifying \( \frac{18}{52} \):
\( x = \frac{9}{26} \)
Now, we need to express the equation in the required form. The equation can be rewritten as:
\( 52x - 9 = 9 \) and \( x \neq \frac{9}{26} \)
Thus, the correct rewrite of the original equation is:
\( 52x - 9 = 9 \) and \( x \neq \frac{9}{26} \)
Among the provided options, none appear to be directly consistent with this. However, if you're looking for a generalized structure, here's the most relevant transformation based on the context of the original question.
Make sure to check which options you need to select based on the context as the above conclusions might differ if any specific condition is set for \( x \).